Analysis of the extension component SAGARPA-INIFAP (2016) in Northern Mexico - Royo Márquez, Mario Humberto; Sierra Tristán, J. Santos; Ronquillo Aboite, Juan Oswaldo; Ochoa Rivero, Jesús Manuel; Vázquez Gómez, Raymundo (Revista Mexicana de Ciencias Agrícolas, 2018)
An analysis of the extension component SAGARPA-INIFAP (2016) is presented in the northern states of Mexico, in relation to value chains or agricultural and fishing/aquaculture species; as well as the target population, territorial distribution, institutional infrastructure of INIFAP, within the North Regional Extension Center (BC, BCS, Coah, Chih, Dgo, NL, Sin, Son, Tam and Zac). The INIFAP and the SAGARPA signed an agreement in May 2016, to support the extension strategy, through training, innovation, monitoring and technical support to extension agents and small producers in the methodological and technical training of innovations. Monthly from May to December, the meetings of the component GT in the states and the GEIT meetings were attended. Five regional meetings of the Northern CRE were organized to monitor and plan the strategy. It is necessary that the GT of the states improve their planning process according to their diagnostic characteristics, which focus the services on: the target population, chains or priority product systems of the region, as well as training needs in the most demanded priority innovations or bottleneck in the UER.